Kinetics on biodiesel oxidation by air oxygen catalyzed by molybdenum complex - Yudaev S. A. Sergey Aleksandrovich; Ivashkina E. N. Elena Nikolaevna; Cherepanova A. D. Anna Dmitrievna; Voronov M. S. Mikhail Sergeevich; Sapunov V. N. Valentin Nikolaevich (2019, 2019)
Title screen